2017
DOI: 10.1186/s12937-017-0228-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multi-modal early oral nutrition for the tolerance of oral nutrition with conventional care after major abdominal surgery: a prospective, randomized, single-blind trial

Abstract: Background & aimsEarly oral nutrition (EON) has been shown to improve recovery of gastrointestinal function, length of stay and mortality after abdominal surgery; however, early oral nutrition often fails during the first week after surgery. Here, a multi-modal early oral nutrition program is introduced to promote recovery of gastrointestinal function and tolerance of oral nutrition.MethodsConsecutive patients scheduled for abdominal surgery were randomized to the multimodal EON group or a group receiving conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
(45 reference statements)
1
19
0
1
Order By: Relevance
“…These findings were unexpected as several recent gene-environment studies observe a significant attenuation of PGS for BMI higher alcohol consumption compared to abstainers. 20 , 23 , 27 However, low-level alcohol use appeared to significantly attenuate the PGS effect among women in a similar manner reported in the literature. Moreover, we observed that higher alcohol consumption had a similar effect on mean BMI as alcohol abstinence across PGS levels in While men.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These findings were unexpected as several recent gene-environment studies observe a significant attenuation of PGS for BMI higher alcohol consumption compared to abstainers. 20 , 23 , 27 However, low-level alcohol use appeared to significantly attenuate the PGS effect among women in a similar manner reported in the literature. Moreover, we observed that higher alcohol consumption had a similar effect on mean BMI as alcohol abstinence across PGS levels in While men.…”
Section: Discussionsupporting
confidence: 79%
“… 22 Moreover, a prior gene-environment interaction study reported that, among women, alcohol intake associated with a higher waist circumference-adjusted BMI; however, higher polygenic risk was associated with a significantly lower body weight for these women. 23 While epidemiologic studies report that many racial/ethnic minority groups, including Black and Latino Americans, are disproportionately affected by the recent upwards obesity trends compared to Whites, these groups remain significantly underrepresented in both the GWAS and gene-environment studies of BMI, with most large cohorts consisting primarily of European-ancestry samples. 24 …”
Section: Introductionmentioning
confidence: 99%
“…The ERAS protocol argues that liquid food on the 2nd hour and solid food intake on the 4th hour of the post-operative period should be encouraged for the patients [1]. Studies conducted in different countries indicate that the earlier oral feeding starts for the patients the shorter the time of the first defecation and the duration of hospital stay is [21,22], not the presence of anastomosis leakage and abscess and the patient satisfaction was high [23]. In laparoscopic colorectal resection surgery, in addition to preoperative oral carbohydrate administration in accordance with ERAs recommendations, patients, who switched to post-operative oral nutrition early had faster recovery of their postoperative clinical functions, decrease in recovery time and decrease in-hospital stay [24].…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, these patients presented with better nutrient intake in the first week after the operation, and time of bowel sounds, flatus, and defecation was shortened in the individuals receiving early ONS. Moreover, these patients remained in the hospital 2 days less, and the total costs were significantly decreased 59 . Sriram et al tested the effects of a nutrition‐focused quality‐improvement program (QIP) on readmissions and LOS in 4 North American hospitals.…”
Section: Discussionmentioning
confidence: 99%